A systematic review of barriers to early presentation and diagnosis with breast cancer among black women. Issue 2 (12th February 2014) - Jones, Claire EL; Maben, Jill; Jack, Ruth H; Davies, Elizabeth A; Forbes, Lindsay JL; Lucas, Grace; Ream, Emma
Abstract : Objective: To explore barriers to early presentation and diagnosis with breast cancer among black women. Design: Systematic review. Methods: We searched multiple bibliographic databases (January 1991–February 2013) for primary research, published in English, conducted in developed countries and investigating barriers to early presentation and diagnosis with symptomatic breast cancer among black women (≥18 years). Studies were excluded if they did not report separate findings by ethnic group or gender, only reported differences in time to presentation/diagnosis, or reported on interventions and barriers to cancer screening. We followed Cochrane and PRISMA guidance to identify relevant research. Findings were integrated through thematic synthesis. Designs of quantitative studies made meta-analysis impossible. Results: We identified 18 studies (6183 participants). Delay was multifactorial, individual and complex. Factors contributing to delay included: poor symptom and risk factor knowledge; fear of detecting breast abnormality; fear of cancer treatments; fear of partner abandonment; embarrassment disclosing symptoms to healthcare professionals; taboo and stigmatism. Presentation appears quicker following disclosure. Influence of fatalism and religiosity on delay is unclear from evidence in these studies. We compared older studies (≥10 years) with newer ones (<10 years) to determine changes over time. In older studies, delaying factors included: inaccessibility of healthcare services; competing priorities and concerns about partner abandonment. Partner abandonment was studied in older studies but not in newer ones. Comparisons of healthy women and cancer populations revealed differences between how people perceive they would behave, and actually behave, on finding breast abnormality. Conclusions: Strategies to improve early presentation and diagnosis with breast cancer among black women need to address symptom recognition and interpretation of risk, as well as fears of the consequences of cancer. The review is limited by the paucity of studies conducted outside the USA and limited detail reported by published studies preventing comparison between ethnic groups.